(untitled) (Research, Society and Development, 2022)
From the National Solid Waste Policy Law (PNRS), in 2010, the way adopted for the waste to be disposed of without contamination was the popularization of sanitary landfills. At the landfill, the waste is interspersed with soil and, on top, there is impermeable soil – a cover layer – to avoid the generation of leachate and the emission of polluting gases. During the research, the oxidative cover layer became a viable alternative in order to reduce the emission of Greenhouse Gases (GHG). For this reason, a bibliographic review of 11 works carried out with this theme in the Solid Waste Group (GRS) was carried out, being of the monograph, dissertation and thesis type, in the range from 2003 to 2019 and a correlation of data from national and international research. The analysis was directed to the results of soil classifications, compaction curves and air and water permeability. According to the results, the addition of organic matter decreases the compressibility of the mixture and improves the stability of the cover layer in the face of climatic variation. In addition, there is an increase in the water retention capacity, improving the performance of the oxidation of methanotrophic bacteria and the impermeable physical barrier. And, as for the compaction, the addition of organic matter indicates a greater ease in the compaction of the mixture. The studies indicated, in addition to the consistency of the results for the application in sanitary landfills and its oxidative potential, the need to add parameters in the analyzes to better support current and future research.